(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Aim - The present study was conducted to determine the prevalence of hypertension in glaucoma patients visiting the ophthalmology outpatient department of a level 3 hospital.Methods- All of the eligible patients were assessed for their glaucoma status by performing slit lamp examination, Goldmann Applanation tonometry, visual acuity and information on blood pressure was collected amongst the patients using a sphygmomanometer.Results- In the present study, Systemic hypertension was found in 66 of the 114 patients which amount to 57.9.Conclusion- The prevalence of hypertension in glaucoma pts was higher and mean intraocular pressure was also higher in hypertension patients.